ANALISIS PENYERAPAN TENAGA KERJA PEREMPUAN DI PROVINSI RIAU - Suci Guszalina; Sri Endang Kornita; Yusni Maulida (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
In the absorption of female workers, there was an increase which in 2021 was 4.57 percent and in 2020 it was 6,16 percent. High population growth has impacted the labor supply, which, if not matched by the demand for labor, will increase unemployment. The occurrence of intellectual unemployment is inseparable from the problem of the world of education which is not able to produce quality workers according to the demands of the labor market so our educated workforce is often unable to compete with foreign workers. Government policies where successful family planning has given women greater free time to participate in the world of work. On the other hand, it can be argued that the desire to increase family income is also quite strong. This study aims to analyze the development and influence of the average wage, education level, and population of women on employment. The method of analysis in this study uses multiple linear regression with the Ordinary Least Square (OLS) technique with the Eviews 10 application, followed by the elasticity method. The results of the analysis in this study are that the average wage/salary of women has a significant and inelastic positive relationship to the absorption of female labor, the average length of education of women has a significant and elastic positive relationship to the absorption of female labor, and the total female population has positive relationship is not significant.